Planejamento espacial marinho de áreas de proteção ambiental do litoral brasileiro - Bolta, Paula Mathias Paulino (2017)
The subjects of sea protection meet in disadvantage in relation to the subjects of terrestrial protection. The challenges and socioeconomic pressures that the sea territory is subject healthy extremely wide. Now the development of the industrial and port activities in the coastal areas, together with the disordered tourism, they generate countless conflicts and use incompatibilities. However, as it guarantees that those and do other activities happen in a certain passage of sea territory in an orderly and maintainable way? Is, it still, preserving and conserving the different coastal and sea habitats and his/her rich biodiversity? In this context, The Protected Marine Areas become primordial strategies for the conservation of biodiversity while they look for to soften the process of environmental degradation. The Marine Spatial Planning is a public process of analysis and allocation regarding the activities that happen in the sea territory in space and temporary scale, seeking to reach maintainable objectives, through political process. It is also considered a process with views to the future and he/she offers tools to solve conflicts and, still, it selects administration strategies to contribute to protect the services necessary ecosystem. The objective of the research is to characterize Marine Spatial Planning in Areas of Protection Environmental Coasts and Navies of Brazilian Northeast. Three APA were selected under administration of ICMBio, inserted in the bioma Atlantic Forest of coastal atmosphere and marine of the Brazilian Northeast: APA Barra do Rio Mamanguape (PB); APA Fernando de Noronha (PE) e APA Costa dos Corais (PE/AL). The respective handling plans and the creation ordinances were analyzed. Besides they were applied questionnaires to the managers of APA, and also interviews with servants of different sections of ICMBio, seeking to obtain information on the process of elaboration of the environmental zoning. In agreement with the analyzes, it was verified that are different necessary approaches for the handing of each UC; standardization lack in criteria of marine zoning, and still administration susceptible to institutional flaws that contemplate in the administration of the sea atmosphere were observed through the research. Being treated of Protected Marine Areas is necessary to understand the three-dimensional and interlinked sea atmosphere in way to the continent; to consider the environmental dynamics and other specificities in the zoning, and still, to foment the social participation and of other institutions of the public power seeking an effective administrations of the marine and coastal atmosphere.